IMPLICATION OF PAIKEM APPROACH WITH SING TO PLAY METHOD IN IMPROVING ENGLISH VOCABULARY IN THE THIRD GRADE STUDENTS ELEMENTARY SCHOOL - rosia, magdalena (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Implication of PAIKEM Approach with Sing to Play Method in Improving English Vocabulary in the Third Grade Students Elementary School. The purpose of this study is to describe the steps of using PAIKEM approach with sing to play method and increase English vocabulary in the third class primay school by using PAIKEM approach with sing to play method. This research used Classroom Action Research (CAR) with colaborative method. Actions observational procedure consists of planning, action, observation, and reflection. Action performing is performed in three cycles, each cycle two appointments. The subjects were elementary school students in third grade state Bumirejo 1 with total 35students. Data collection techniques using observation, interviews, and tests. Data analysis using qualitative analysis data technique. The validation of data is using triangulation technique. The conclusions showed PAIKEM approach with sing to play method can increase English vocabulary  for the third grade students state elementary school. According to the result can to be known complete student percentage experience increased which is of condition of startup 23,00% as 91,87% on I cycle, on cycle II experience step-up as 82,60%, and on III cycle as 95,%. Keywords: PAIKEM, sing to play, vocabulary, English Abstrak: Penerapan Pendekatan PAIKEM dengan Metode Sing to Play dalam Peningkatan Pemahaman Kosakata Bahasa Inggris Siswa Kelas III SD Negeri 1 Bumirejo. Tujuan penelitian ini adalah untuk menjelaskan langkah-langkah penerapan pendekatan PAIKEM dengan Metode sing to play dan meningkatkan pemahaman kosakata Bahasa Inggris Siswa Kelas III SD menggunakan Pendekatan PAIKEM dengan metode Sing to Play. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas, dengan teknik kolaboratif. Prosedur penelitian tindakan kelas berupa perencanaan, pelaksanaan, pengamatan, dan refleksi. Pelaksanaan tindakan dilaksanakan dalam tiga siklus, masing-masing siklus dua pertemuan. Subjek penelitian siswa kelas III SD Negeri 1 Bumirejo semester 2 sejumlah 35 siswa. Teknik pengumpulan datanya observasi, wawancara, dan tes. Analisis data menggunakan analisis data kualitatif. Validitas data menggunakan teknik triangulasi. Hasil penelitian menunjukan penggunaan pendekatan PAIKEM dengan metode Sing to Play dapat meningkatkan pemahaman kosakata bahasa Inggris siswa kelas III SD. Berdasarkan penilaian hasil diketahui persentase siswa yang tuntas mengalami peningkatan yaitu dari  kondisi awal 23,00% menjadi 91,87% pada siklus I, pada siklus II mengalami peningkatan menjadi 82,60%, dan pada siklus III menjadi 95,41%.Kata Kunci: PAIKEM, sing to play, kosakata, bahasa Inggris.